From Cinderella to CEO : - Broussard, Cary J (John Wiley & Sons, 2006)
Broussard, an executive at a "traditional Southern-based" travel hospitality corporation, uses 10 fairy tales, their handsome princes and huntsmen removed, to illustrate ways women can find greater success at work. It's not quite the same as spinning straw into gold, but the principles she advocates-staying focused and working well with others-can transform an abominable worklife. Though the book's conceit can seem saccharine, Broussard's stories don't shirk the dark side of fairy tales; the poisoned apples, wicked wolves and villains become sadistic bosses, jealous coworkers and insubordinate underlings. Broussard argues against the widely-held notion that female bosses are more likely to resent ambitious women subordinates and downplays workplace jealousy among women, instead positing "the evil queen might be a man." The result is a deliberately non-threatening chorus of female empowerment, with tips on how to navigate office politics and advance your career. She sometimes shoehorns discussions of multiculturalism, sexual harassment and creating a professional wardrobe into ill-fitting fairy tales, and neologisms such as "fairy godmentor" may annoy some readers, but women looking for easy-to-digest workplace motivation and gender-specific affirmation will find it here.